Treatment of osteonecrosis of the femoral head with free vascularized fibular grafting: Results of 7.6-year follow-up - Mehmet Bekir Ünal; Eren Cansu; Fatih Parmaksızoğlu; Hakan Cift; Serkan Gürcan (Acta Orthopaedica et Traumatologica Turcica)
Objectives: The aim of this study was to determine long term follow up of the patients who had femoral head osteonecrosis and had been treated with free vascularized fibular grafting. Patients and methods: We retrospectively reviewed 28 hips of 21 patients who had undergone free vascularized fibular grafting for the treatment of osteonecrosis of femoral head. There were 16 male and 5 female patients. The mean age of the patients at the time of surgery was 30.7 years (between 15 and 53 years). The mean follow-up time was 7.6 years (between 5 years and 9.2 years). Results: During follow-up, one patient died because of leukemia, and one patient was lost. The remaining 26 hips of 19 patients were evaluated. According to the Ficat classification, at the time of surgery, 17 hips were in grade 2 and 9 hips were in grade 3. The post-operative Harris hip scores in grade II disease were excellent in 12 patients, good in 3 patients, and fair in 1 patient. In grade III disease, 1 patient was excellent, 5 patients were good, and 1 patient was fair. There was a significant increase in HHS scores (61 ± 9.7 vs 84 ± 17.8, p < 0.001). Conclusion: Free vascularized fibular grafting yields extremely good results, particularly in pre-collapse stages of disease in young patients. The operation time does not mark increased if the surgical team is “familiar” with the procedure, and the residual fibular defect of the donor site does not impair the functions of daily living. Level of Evidence: Level IV, Therapeutic study. Keywords: Osteonecrosis of the femoral head, Free vascularized fibular grafting